Cognitive and psychophysiological impact of surgical mask use during university lessons (2021)
The aim of the present study was to analyze the impact of surgical mask use in cognitive and psychophysiological response of university students during a lesson. We analyzed 50 volunteers university students (age 20.2 ± 2.9) in two 150 min lessons. i. personal class using a surgical mask and ii. online class with student at home without the mask. Blood oxygen saturation, heart rate and heart rate variability, mental fatigue and reaction time were measured before and immediately after both lectures. We found how both lesson produced an increase in mental fatigue, reaction time and autonomous sympathetic modulation, being heart rate significantly higher (77.7 ± 18.2 vs. 89.3 ± 11.2 bpm, not mask, mask respectively) and blood oxygen saturation significantly lower (98.4 ± 0.5 vs. 96.0 ± 1.8%, mask, not mask respectively) using the surgical mask. The use of surgical mask during a 150 min university lesson produced an increased heart rate and a decrease in blood oxygen saturation, not significantly affecting the mental fatigue perception, reaction time and time, frequency and nonlinear hear rate variability domains of students